2017
DOI: 10.1371/journal.pone.0168890
|View full text |Cite
|
Sign up to set email alerts
|

Soil, Leaf and Root Ecological Stoichiometry of Caragana korshinskii on the Loess Plateau of China in Relation to Plantation Age

Abstract: Caragana korshinskii, a leguminous shrub, a common specie, is widely planted to prevent soil erosion on the Loess Plateau. The objective of this study was to determine how the plantation ages affected soil, leaf and root nutrients and ecological stoichiometry. The chronosequence ages of C. korshinskii plantations selected for this study were 10, 20 and 30 years. Soil organic carbon (SOC) and soil total nitrogen (STN) of C. korshinskii plantations significantly increased with increase in the chronosequence age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 37 publications
3
44
2
Order By: Relevance
“…Afforestation of drylands by nitrogen‐fixing shrubs is widely expected to soil carbon sequestration by alleviating nitrogen shortages (Houlton et al, ). Numerous studies have demonstrated that afforestation of legume shrubs increase soil carbon and nitrogen sinks synchronously (Resh, Dan, & Parrotta, ; Shi et al, ; Zeng et al, ). However, our results indicated that initial elevated STN stock by afforestation was decreased in older plantations, indicating a limiting effect on long‐term carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Afforestation of drylands by nitrogen‐fixing shrubs is widely expected to soil carbon sequestration by alleviating nitrogen shortages (Houlton et al, ). Numerous studies have demonstrated that afforestation of legume shrubs increase soil carbon and nitrogen sinks synchronously (Resh, Dan, & Parrotta, ; Shi et al, ; Zeng et al, ). However, our results indicated that initial elevated STN stock by afforestation was decreased in older plantations, indicating a limiting effect on long‐term carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Afforestation soil may accumulate low‐quality plant litter input with rich recalcitrant carbon, causing slower microbial decomposition, and ultimately decrease soil nitrogen stock (Li, Zhu, Zhang, & Cheng, ; Templer, Groffman, Flecker, & Power, ). Nevertheless, enriched leaf nitrogen of C. korshinskii with plantation ages and its relatively labile litter in the adjacent locations (Zeng et al, ) suggested that afforestation‐induced recalcitrant carbon input was unlikely a mechanism regulating the negative STN stock response. Alternatively, plant with high nitrogen residence time reduces the annual flux of nitrogen from the plant pool back to the soil pool (Laungani & Knops, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And the rare researches that pay attention to desert ecosystems. Many researches contents is about the C, N, P concentrations and the ratios of plants at the organ and individual levels, which also get the results that C, N, P concentrations and their ratios of different organs were significantly different, the different individuals too (Zeng Q et al . 2017; Halvorson H M et al .…”
Section: Introductionmentioning
confidence: 99%